The brain drain, educated unemployment, human capital formation, and economic betterment - Oded Stark; C. Simon Fan (University of Bonn, Center for Development Research (ZEF), 2007)
Extending both the harmful brain drain literature and the beneficial brain gain literature, this paper analyzes both the negative and the positive impact of migration by skilled individuals in a unified framework. The paper extends the received literature on the harmfulbrain drain by showing that in the short run, international migration can result in educated unemployment and overeducation in developing countries, as well as a brain drain from these countries. A simulation suggests that the costs of educated unemployment and overeducation can amount to significant losses for the individuals concerned, who may constitute a substantial proportion of the educated individuals. Adopting a dynamic framework, it is then shown that due to the positive externality of the prevailing, economy-wide endowment of human capital on the formation of human capital, a relaxation in migration policy in both the current period and the preceding period can facilitate take-off of a developing country in the current period. Thus, it is suggested that while the migration of some educated individuals may reduce the social welfare of those who stay behind in the short run, it improves it in the long run. – – In diesem Aufsatz analysieren die Autoren den negativen als auch den positiven Einfluss der Migration qualifizierter Individuen in einem vereinheitlichten Rahmen, wobei an die bestehende Literatur sowohl zum ”nachteiligen Braindrain” als auch zum ”vorteilhaften Braingain” angeknüpft und diese jeweils erweitert wird. Die Autoren zeigen, dass internationale Migration in Entwicklungsländern kurzfristig zu Arbeitslosigkeit unter gut ausgebildeten Arbeitskräften und zu einem Überangebot an Bildung sowie zu einem Braindrain aus diesen Ländern führen kann. Die Ergebnisse einer Simulation legen nahe, dass die Kosten, die durch Arbeitslosigkeit von Hochqualifizierten und "Überbildung" verursacht werden, zu signifikanten Einbußen bei den betroffenen Individuen führen können. Durch Verwendung eines dynamischen Modells wird gezeigt, dass aufgrund des positiven Effektes, den eine gute Ausstattung mit Humankapital auf die Bildung von Humankapital hat, eine Entspannung in der Migrationspolitik den Take-off eines Entwicklungslandes bewirken kann. Hieraus lässt sich schlussfolgern, dass obwohl die Migration einiger gebildeter Individuen die öffentliche Wohlfahrt derer eventuell einschränkt, die kurzfristig zurückbleiben, wird sie diese langfristig verbessern.
Keywords: 330; Brain Drain; Überqualifikation; Arbeitslosigkeit; Kosten-Nutzen-Analyse; Entwicklungsländer